Penetrating aortic ulcer following endoscopic dilatation of esophageal anastomotic stenosis: a case report - Yang, Jingjing; Wang, Qinghua; Han, Wei (Frontiers in Surgery, 2025)
BackgroundEndoscopic balloon dilation serves as the first-line treatment for anastomotic strictures after esophagectomy. While generally safe, the procedure can, in rare instances, lead to severe vascular complications.Case presentationA 64-year-old male with a prior history of esophagectomy for cancer presented with dysphagia due to an anastomotic stricture. Shortly after undergoing endoscopic balloon dilation, he developed hoarseness. Computed tomography (CT) identified a penetrating aortic ulcer (PAU) with contained rupture and an associated hematoma compressing the left recurrent laryngeal nerve, consistent with Ortner's syndrome. The patient was successfully managed with emergent thoracic endovascular aortic repair (TEVAR). At the three-month follow-up, the aortic stent remained, and his hoarseness had significantly improved.ConclusionThis rare case of a PAU and Ortner's syndrome following endoscopic dilation underscores the critical importance of vigilance for life-threatening vascular injuries after seemingly routine procedures. It highlights the necessity of considering such complications in the differential diagnosis of post-procedural symptoms and demonstrates the efficacy of endovascular repair as a definitive treatment option.